Upholding National and Cultural Identity in the Works of Jhumpa Lahiri - ., Neha (Journal of Ecohumanism, 2025)
This paper explores the themes of cultural identity, national identity and feminist consciousness in the works of Jhumpa Lahiri, focusing on her depiction of the Indian diaspora in the United States. By examining narratives such as Interpreter of Maladies, The Namesake, and selected short stories, the study highlights how Lahiri portrays the complex interplay between heritage, migration, and personal identity. The analysis emphasizes the ways in which cultural rituals, domestic practices, and historical memory shape the psychological and emotional experiences of immigrants. Additionally, the paper investigates Lahiri’s subtle feminist perspective, revealing the challenges faced by Indian women negotiating family, tradition, and selfhood in transnational contexts. Ultimately, Lahiri’s fiction illuminates the dynamic processes of identity formation and belonging in a globalized world, demonstrating the enduring significance of culture, nation, and gender in shaping human experience.